THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN BUILDING A POSITIVE IMAGE OF THE COMPANY: A LITERATURE REVIEW - Loso Judijanto; Al-Amin (ADISAM Publisher, 2024)
In the era of globalisation and increasing socio-environmental awareness, CSR has become an important component of corporate business strategy. This study uses the literature method. The results show that CSR has a significant impact in shaping the company's positive image, provided that the CSR programme is implemented authentically, strategically, and sustainably. The study also identified key factors in the success of CSR, including alignment with corporate values, transparency, stakeholder engagement, and effective communication. The findings provide valuable insights for business practitioners and researchers in understanding the strategic role of CSR in building and maintaining a positive corporate image in an increasingly complex and competitive business environment.